When "small" is "beautiful" - Evens, Tom (Javnost (Ljubljana), 2011)
In this article, the focus is on how policy makers in Flanders (Belgium) can be inspired by the implementation of local radio development strategies in three neighbouring markets (the Netherlands, Great-Britain, the French speaking Community in Belgium). More specific, the article concentrates on the questions of which options policy makers have at their disposal in supporting local radio and what lessons they should learn from foreign experiences in boosting the sectorŽs development. The final aim is to come up with policy recommendations for reorganising local broadcasting and strengthening its economic and social value. To do this, document analysis was combined with seventeen local radio expert interviews in all markets involved. Next, a cross-country analysis was performed to identify structural conditions and propose policy options for a proactive media policy regarding small-scale radio.
Keywords: Europe; Evropa; radio; lokalne skupnosti; radijske postaje